PENDAFTARAN PERALIHAN HAK ATAS TANAH KARENA JUAL BELI YANG DIBUAT DIBAWAH TANGAN (STUDI KASUS PUTUSAN NO. 116/PDT.G/2019/BKN) - Rurrie Putri Mutiara Sari; Dinda Keumala (Fakultas Hukum Universitas Trisakti, 2021)
The transfer of land rights in a sale and purchase must be carried out in front of an authorized official (PPAT) by making a Sale and Purchase Deed as evidence for the process of transferring land rights/title at the Land Office. The formulation of this research problem is how is the validity of the transfer of land rights due to the sale and purchase of land made under the hand? What must the buyer do to register the transfer of land rights made under the hand based on Decision No. 116/Pdt.G/2019/Bkn? Normative juridical research method. Secondary data collection technique. The nature of the research used is descriptive analytical. This research is analyzed qualitatively. The method of drawing conclusions with the deductive logic method. The results of research, discussion and conclusions, especially in the case of Decision No.116/Pdt.G/2019/Bkn Bangkinang that the sale and purchase of land under the hand is valid because it has fulfilled the material requirements in buying and selling, but has not fulfilled the formal requirements because the sale and purchase is carried out only with a letter under the hand, a Sale and Purchase Deed has not been made before a PPAT.